Handbook of cyanobacterial monitoring and cyanotoxin analysis - Meriluoto, Jussi; Spoof, Lisa; Codd, G. A. (John Wiley & Sons, Inc., 2017)
A valuable handbook containing reviews, preactical methods and standard operating procedures. A valuable and practical working handbook containing introductory and specialist content that tackles a major and growing field of environmental, microbiological and ecotoxicological monitoring and analysis Includes introductory reviews, practical analytical chapters and a comprehensive listing of almost thirty Standard Operating Procedures (SOPs) For use in the laboratory, in academic and government institutions and industrial settings.